2013
DOI: 10.1155/2013/369016
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Optimization of Evacuation Routes in Stadium Using Superposed Potential Field Network Based ACO

Abstract: Multiobjective evacuation routes optimization problem is defined to find out optimal evacuation routes for a group of evacuees under multiple evacuation objectives. For improving the evacuation efficiency, we abstracted the evacuation zone as a superposed potential field network (SPFN), and we presented SPFN-based ACO algorithm (SPFN-ACO) to solve this problem based on the proposed model. In Wuhan Sports Center case, we compared SPFN-ACO algorithm with HMERP-ACO algorithm and traditional ACO algorithm under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…An extra dimension that could to be recognised is the individual variation (or heterogeneity) in strategy choosing that also could be subjected to tests of optimality using numerical analyses [79][80][81]. This stream of behavioural optimisation studies can be regarded as a complementary domain to that of the architectural optimisations that seek to facilitate evacuations through physical modifications of the environment (as opposed to the behaviour of evacuees) [82][83][84][85] or the approach of route-planning optimisations [67,[86][87][88][89][90][91][92][93][94].…”
Section: Summary Discussion and Future Researchmentioning
confidence: 99%
“…An extra dimension that could to be recognised is the individual variation (or heterogeneity) in strategy choosing that also could be subjected to tests of optimality using numerical analyses [79][80][81]. This stream of behavioural optimisation studies can be regarded as a complementary domain to that of the architectural optimisations that seek to facilitate evacuations through physical modifications of the environment (as opposed to the behaviour of evacuees) [82][83][84][85] or the approach of route-planning optimisations [67,[86][87][88][89][90][91][92][93][94].…”
Section: Summary Discussion and Future Researchmentioning
confidence: 99%
“…Court. During the investigation, it was found that the lighting methods of the school's gymnasium badminton court mainly include complete natural lighting, combination of natural lighting and artificial lighting, and complete artificial lighting [16][17][18][19]. In most cases, the badminton court in the gymnasium of our school only relies on natural lighting and artificial lighting.…”
Section: Illumination Data Analysis Of Each Area Of the Badmintonmentioning
confidence: 99%
“…In both technical practice and theoretical research, there are a large number of multi-objective optimization (MOP) problems that need to be optimized synchronously for multiple objectives [1][2][3]. When solving multi-objective optimization problems, the traditional method is to convert this problem into a single-objective problem based on prior knowledge and to use single-objective optimization methods to obtain a satisfactory Pareto optimal solution [4].…”
Section: Introductionmentioning
confidence: 99%